Inhibition of local effects induced by Bothrops erythromelas snake venom: Assessment of the effectiveness of Brazilian polyvalent bothropic antivenom and aqueous leaf extract of Jatropha gossypiifolia. (January 2017) - Félix-Silva, Juliana; Gomes, Jacyra A.S.; Xavier-Santos, Jacinthia B.; Passos, Júlia G.R.; Silva-Junior, Arnóbio A.; Tambourgi, Denise V.; Fernandes-Pedrosa, Matheus F.
Abstract: Bothrops erythromelas is a snake of medical importance responsible for most of the venomous incidents in Northeastern Brazil. However, this species is not included in the pool of venoms that are used in the Brazilian polyvalent bothropic antivenom (BAv) production. Furthermore, it is well known that antivenom therapy has limited efficacy against venom-induced local effects, making the search for complementary alternatives to treat snakebites an important task. Jatropha gossypiifolia is a medicinal plant widely indicated in folk medicine as an antidote for snakebites, whose effectiveness against Bothrops jararaca venom (BjV) has been previously demonstrated in mice. In this context, this study assessed the effectiveness of the aqueous extract (AE) of this plant and of the BAv against local effects induced by B. erythromelas venom (BeV). Inhibition of BeV-induced edematogenic and hemorrhagic local effects was assayed in mice in pre-treatment (treatment prior to BeV injection) and post-treatment (treatment post-envenomation) protocols. Inhibition of proteolytic, phospholipase A2 (PLA2 ) and hyaluronidase enzymatic activities of BeV were evaluated in vitro . BAv cross-reactivity and estimation of antibody titers against BeV and BjV were assessed by Ouchterlony double diffusion test. The results show that in pre-treatment protocol AE and BAv presented very similar effects (about 70% of inhibition for edematogenic and 40% for hemorrhagic activities). However, BAv poorly inhibited edema and hemorrhage in post-envenomation protocol, whilst, in contrast, AE was significantly active even when used after BeV injection. AE was able to inhibit all the tested enzymatic activities of BeV, while BAv was active only against hyaluronidase activity, which could justify the low effectiveness of BAv against BeV-induced local effects in vivo . Ouchterlony's test showed positive cross-reactivity against BeV, but the antibody titers were slightly higher against BjV. Together, these data indicate that despite the presence of immunological cross-reactivity, Brazilian polyvalent bothropic antivenom presented low inhibitory potential against biological and enzymatic effects of BeV, illustrating the need for new strategies in the production of antivenom with broad neutralizing potential in the treatment of Bothrops spp. envenomation throughout the country. Together, the results highlight the antiophidic potential of J. gossypiifolia, suggesting that it can be considered a potential adjuvant in the treatment of bothropic envenomation local effects. Graphical abstract: Highlights: Despite immunological cross-reactivity with BeV, BAv was poorly active against local and enzymatic activities of this venom. AE inhibited efficiently local effects and enzymatic activities induced by BeV. This study demonstrates the significant potential of this medicinal plant as a promising adjuvant in antivenom therapy.